The Drilling Guiding Templates and Pre-Bent Titanium Plates Improves the Operation Accuracy of Orthognathic Surgery With Computer-Aided Design and Computer-Aided Manufacturing Occlusal Splints for Patients With Facial Asymmetry. Issue 7 (October 2019) - Hu, Pei; Li, Jiayang; Du, Wen; Ji, Huanzhong; Xu, Chunwei; Luo, En
Abstract : Abstract: Facial asymmetry is a common maxillofacial deformity which requires surgery to recover the 3-dimensional relationship of bones. The computer-aided design and computer-aided manufacturing (CAD/CAM) has been developed and applied to improve orthognathic analysis and surgery design. How to accurately realize the preoperative design of orthognathic surgery with CAD/CAM occlusal splints during operation remains a big problem. In this study, 24 consecutive patients with facial asymmetry were recruited and assigned to 2 groups. For Group A, CAD/CAM was applied to designing and producing not only the occlusal splints, but also the drilling guiding templates and pre-bent titanium plates, and for Group B CAD/CAM was applied for occlusal splints only. Postoperative clinical examinations, symmetry evaluation through 3D cephalometric analysis, accuracy comparison using color distance maps and quantitative accuracy analysis were performed. Symmetry evaluation showed that patients of both groups achieved improved facial symmetry after surgery. The color distance maps and quantitative accuracy analysis together demonstrated significantly less difference found between virtual simulated surgery and postoperative CT scan data in Group A than in Group B. In conclusion, by navigation with the drilling guiding templates and pre-bent titanium plates, the facial symmetry for patients with facial asymmetry was successfully restored after orthognathic surgery, same as applying CAD/CAM occlusal splints only. However, the drilling guiding templates and pre-bent titanium plates would provide a more accurate performance according to preoperative simulation, especially for proximal mandibular segments. Abstract : Supplemental Digital Content is available in the text